Intensive Care Management of Eclampsia Complicated with Acute Kidney Injury: A Case Report - Liliriawati Ananta Kahar; Wiwi Monika Sari; Rizky Rivonda Bennovry; Muhammad Ryfki Syahredi Adnani (HM Publisher, 2023)
Background: Pre-eclampsia-related AKI occurs in 21% of all pregnancies, with 4% associated with severe eclampsia. The most common cause of AKI is eclampsia, which affects about 3-5% of pregnancies. Case presentation: The patient came to the hospital with seizures three times at home, whole body seizures, duration 1-2 minutes, and after a seizure, the patient was unconscious. The patient had a seizure in the hospital twice, 5-10 minutes. She has had a history of hypertension during pregnancy (210/112 mmHg). The patient was diagnosed with decreased consciousness due to eclampsia antepartum on Primipara 31-32 weeks of preterm pregnancy on a maintenance dose of MgSO4 regimen + oligohydramnion patient was performed emergency section cesarean. After Termination, the patient was admitted to ICU. The patient was assisted by a mechanical ventilator. Conclusion: Critical care management is necessary for eclampsia with Acute Kidney Injury, adequate initial management, including hemodynamic stabilization, fluid balance, electrolyte correction, and possibly dialysis, is required to reduce morbidity and mortality.